Pemanfaatan Teknologi Open Source pada Perpustakaan Sebagai Alternatif Penanggulangan Problema Kelestarian Dokumen - Hapnes Toba (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2004)
Using information technology applications in real life situation could give manyadvantages. One such advantages can be seen in library collection management. Building anapplication for the library management system could be done in low cost, efficient andflexible manner through the using of open sources technology. This article describes aninitiatiave and architectural design of an online electronic document management system atthe Library of Engineering Faculty Maranatha Christian University Bandung, through theusing of open-sources and e-content technology. The second part of this article gives a list ofproblems that should be anticipated to ensure that electronic documents can be useful notonly today but also in the future. Long-term preservation strategy through the using of XMLtechnology is a good possible solution for document preservation problem. This strategy hasbeen observed and evaluated in many research projects in the past 5 years.Keywords: digital library, open sources technology, document preservation, metadata, econtent.